The Characteristics of TCM Clinical Trials: A Systematic Review of ClinicalTrials.gov - He, Yingchun; Lv, Yinghua; Li, Jordan V.; Huang, Jihan; Chen, Junchao; Zheng, Qing-shan (Evidence-based complementary and alternative medicine, 2017)
Objective. The aim of this review is to characterize current status of global TCM clinical trials registered in ClinicalTrials.gov. Methods. We examined all the trials registered within ClinicalTrials.gov up to 25 September 2015, focusing on study interventions to identify TCM-related trials, and extracted 1,270 TCM trials from the data set. Results. Overall, 691 (54.4%) trials were acupuncture, and 454 (35.8%) trials were herbal medicines. Differences in TCM trial intervention types were also evident among the specific therapeutic areas. Among all trials, 55.7% that were small studies enrolled <100 subjects, and only 8.7% of completed studies had reported results of trials. As for the location, the United States was second to China in conducting the most TCM trials. Conclusion. This review is the first snapshot of the landscape of TCM clinical trials registered in ClinicalTrials.gov, providing the basis for treatment and prevention of diseases within TCM and offering useful information that will guide future research on TCM.